Mamdani Fuzzy Expert System Based Directional Relaying Approach for Six-Phase Transmission Line - Kumar, Naresh; Sanjay, Ch.; Chakravarthy, M (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
Traditional directional relaying methods for 6-phase transmission lines have complex effort, and so there is still a need for novel direction relaying estimation scheme. This study presents a Mamdani-fuzzy expert system (MFES) approach for discriminating faulty section/zone, classifying faults and locating faults in 6-phase transmission lines. The 6-phase fundamental component of currents, voltages and phase angles are captured at single bus and are used in the protection scheme. Simulation results substantiate that the protection scheme is very successful against many parameters such as different fault types, fault resistances, transmission line fault locations and inception angles. A large number of fault case studies have been carried out to evaluate reach setting and % error of proposed method. It provides primary protection to transmission line length and also offers backup protection for a reverse section of transmission line. The experimental results show that the scheme performs better than the other schemes.
Keywords: simulation; fuzzy; fault protection; transmission lines; IJIMAI